Pengaruh Jingle Iklan Teh Botol Sosro di RCTI terhadap Pengingatan Merek Barang pada Pemirsa Remaja Pelajar SMUN Bandung - Nurrahmawati Nurrahmawati (MediaTor (Jurnal Komunikasi), 2002)
This research was intended to know the amount ofverbaI and nonverbal message s influence in thejingle ads, both partially and simultaneously, on the teenager s attention and retention toward product brand. As a kind ofcausality research. which was conducted with survey method, this research was located in Bandung Town District, with some High Senior School students as its respondents. The sampling techniques usedfor this research was random sampling techniques and Path Analysis as its toolfor data analysis. In general, this research concluded that messagefactor hadsome influences on the teenagers attention toward the Teh Botol Sosro s ad. On the other hand, the attention influenced brand retention as well. Therefore, in general, commercialjingle variables which are carried through intermediary variable (which is, attention), gave a relatively significant influence toward the teen s brand retention. Meanwhile, verbal messagefactor provided less meaningful influence. Based on the research result, it was concluded that the verbal and nonverbal message factors in the commercia/jingle simultaneously aroused teenager s retention toward the ads. That attention could arousing teenager retention then toward the product brand as well. Nonverbal message implied on the commercialjingle partially aroused the teen s attention toward the ad, meanwhile the verbal message on the same commercial didn ~ arouse the same attention toward the Teh Botol Sosro sad. More originality, variations and uniqueness are needed in arranging a copywritingfor such and in order to attract more attentionfrom teenager audience.